2016
DOI: 10.1093/rheumatology/kew457
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative immunosuppressant exposure is associated with diversified cancer risk among 14 832 patients with systemic lupus erythematosus: a nested case–control study

Abstract: Diverse cancer risks are associated with different immunosuppressants in patients with SLE. CYC increases the risk of cancer, and HCQ decreases this risk in SLE patients, both in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
3
46
0
2
Order By: Relevance
“…A protective function of antimalarial against cancer in SLE patients has been proposed [38]. Hsu et al found that HCQ decreased cancer risk in a dose-dependent manner [21]. Our current large-scale study has also elucidated a negative association between HCQ and cancer.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…A protective function of antimalarial against cancer in SLE patients has been proposed [38]. Hsu et al found that HCQ decreased cancer risk in a dose-dependent manner [21]. Our current large-scale study has also elucidated a negative association between HCQ and cancer.…”
Section: Discussionsupporting
confidence: 65%
“…A different research reported that exposure to CTX might contribute to a higher lymphoma risk in SLE patients [19], although this was contradicted by a different report showing that the use of CTX and AZA did not contribute to lymphoma risk [20]. It has been demonstrated that CTX increases cancer risk in SLE patients in a dose-dependent manner [21]. Therefore, more investigations looking at a larger number of participants is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relation between SLE and GC has not been fully elucidated; the mechanism may be as follows: (a) Patients with SLE have an increased risk of developing tumors, possibly related to the disease itself . Literature reports also showed the development of tumor was related to the use of immunosuppressive agents, especially cyclophosphamide . (b) Tumors trigger immune abnormalities presented with varieties of rheumatoid lesions, including inflammatory myopathy, arthritis, vasculitis and SLE .…”
Section: Discussionmentioning
confidence: 99%